Use of Marsupialization as a Definitive Treatment for Large-sized Dentigerous Cysts in a Patient with Mucopolysaccharidosis Type I - de Menezes, Pedro Henrique Moraes; Teixeira, Maria Clara Corrêa de Almeida; Fernandes, Cleone de Fátima Oliveira Neder; Bastos, Marden Oliveira; Oliveira, Marina Reis; Mariano, Ronaldo Celio (Prague medical report, 2024)
The correct diagnosis is fundamental for the appropriate treatment to be employed in a particular pathology. The best treatment is not the one that solves only local problems, fragmenting the patient, and therefore, it is necessary to integrate the entire systemic condition of the individual before initiating any local treatment. This context inevitably requires dentistry to participate in a multidisciplinary approach, where the role of the dentist is expanded in concepts that encompass ethics, human dignity, and professional valorization. This article describes a clinical case of a patient with mucopolysaccharidosis type I, whose treatment of cystic lesions present in the mandible was exclusively performed through marsupialisation. The objective of this study is to demonstrate, within the complexity of this rare syndrome, the difficulties of diagnosis and the need for evaluation of the patient beyond the limits of the oral cavity, as well as to report two cases of large dentigerous cysts, surgically treated conservatively through marsupialisation, without the need for re-approach for enucleation and without recurrences over a 20-year period.
Keywords: Dentigerous cyst; nemoci mandibuly; Dental retentions; Mucopolysaccharidosis I; dentigerózní cysta; Dentigerous Cyst; Humans; Marsupialization; mukopolysacharidóza I; Mandibular Diseases; lidé; Mucopolysaccharidosis type I